UPAYA PENINGKATAN DISIPLIN SISWA SMK NEGERI 2 MADIUN TAHUN PELAJARAN 2015/2016 DALAM MENGURANGI PELANGGARAN TATA TERTIB SEKOLAH MELALUI METODE DISKUSI DAN BRAIN STORMING PADA LAYANAN KONSELING KELOMPOK - Erna Puji Lestari (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2016)
The method used in this case is the method of discussion and Brain Storming (brainstorming). Application of this method is that there is a problem every student should mention general problems experienced in school or problems in general about violations of school rules that often do. Then the other students had to submit a proposal submitted his problem solving. It is expected that way; students realize that they have the same problem, and they were able to give an opinion to resolve the issue. This research was carried out on some foster students SMK Negeri 2 Madiun in the academic year 2015/2016. This troubled foster students amounted to 12 students, which is a combination of several classes into foster student counselor. This study uses two cycles with each cycle consisting of planning, implementation, observation, and reflection. The instrument used was a data documentation, questionnaire sheet student, and teacher observation sheet. Results of the study are the decreasing number of violations committed by students with observational data indicated. While data from subject teachers, also showed an increase in student learning outcomes obtained significantly with increasing levels of discipline that do. The conclusion of this study is the group counseling services are performed by using the methods of learning and brain Storming discussion on some foster students at SMK Negeri 2 Madiun in the academic year 2015/2016 can be successful in increasing violations of discipline by reducing school discipline.